Long Distance Solidarity: Polish Public Opinion and the Boer War 1899–1902 - Szlanta, Piotr (Werkwinkel, 2017)
The bloody conflict which was taking place in South Africa in the years 1899-1902 was followed with a great interest by Polish public opinion. Its greatest part strongly sympathized with the Boer republics. Their burgers were idealized and presented by the Polish press as brave fighters for independence, who dared to stand up against the world empire to defend their rights while Great Britain was attributed full responsibility for the outbreak of the war. For many Poles the Boers personified the general idea of freedom fighters and symbolized all suppressed nations. Their sad fate seemed to be quite similar to the Polish one and this similarity was the main source of sympathy toward defenders of the Transvaal and Free Orange State. Voices of few Polish intellectuals, who called for a more objective and not so emotional view on the war, could not change the pro-Boers stance of the greatest part of Polish public opinion.